Detection of Colorectal Cancer Specific APC Deletion in Peripheral Blood Culture in Iraqi Population by FISH Technique - Haidar J. Muhammed (Journal of Global Pharma Technology, 2017)
Colorectal cancers (CRC) are classified as tumor phenotypes based on molecular profiles in which the most common defect is inactivation of adenomatous polyposis coli (APC) gene. This study included (20) patients male and female suffered from tumor of CRC range aged less than 20 and farther 60 years compared with (5) healthy individuals as a control. Samples collected from colonoscopy unit from Baghdad Teaching hospital and National Center Hospital for early detection of cancer related to Ministry of Iraqi Health. Deletion of APC gene was further verified on chromosomal level on metaphase spreads by peripheral blood lymphocytes (PBLs) culture so as value screening by using fluorescence in situ hybridization (FISH) technique. The results described the identification of classical familial adenomatous polyposis (FAP), attenuated familial adenomatous polyposis (AFAP) and sporadic colorectal cancer as in58.3%, 25%,and 16.7 % respectively which were showed significant differences (P≤0.01) compared with healthy control, so as a deletion of arm specific 5q of APC gene which showed significant differences (P≤0.01). In conclusion of this study explained the APC gene alteration localized on 5q arm have an essential role in prognosis and prognostic of colorectal cancer.Keywords: APC gene, 5q arm chromosome, AFAP and FAP gene incolorectal cancer.